PENGARUH MODEL PEMBELAJARAN ACTIVE LEARNING TIPE STORYTELLING EKSPRESIF TERHADAP KEPERCAYAAN DIRI PESERTA DIDIK PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS X DI MA NIHAYATUL AMAL RAWAMERTA KARAWANG - Nur Habibah, Elia; Nabilatul Fauziah, Debibik; Ulya, Neng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low confidence of students in learning Islamic Cultural History (SKI), which is shown by the lack of courage of students in asking questions, expressing opinions, and appearing in front of the class. This condition causes students to tend to be passive in the learning process, so a learning model is needed that is able to encourage active student involvement. This research was carried out at MA Nihayatul Amal Rawamerta Karawang, based on the results of initial observations, it was found that students' confidence still needs to be improved and has not fully provided space for students to actively participate. This study uses a quantitative approach with an experimental method with a one group pretest-posttest design. The research sample amounted to 48 students in classes X A and X C, data collection techniques were carried out through questionnaires, observations, and documentation, while the data analysis used descriptive analysis tests and inferential analysis with the Shapiro-Wilk normality test and the Paired Sample t-test. The results of the study showed that the average confidence of students increased from 88.50 in the pretest to 95.48 in the posttest. The results of the hypothesis test obtained a significance value of 0.000 < 0.05, which shows a significant difference between the pretest and posttest scores. Based on the results of the study, it can be concluded that the Expressive Storytelling type Active Learning learning model has a positive and significant effect on students' confidence in learning Islamic Cultural History class X at MA Nihayatul Amal Rawamerta Karawang.